2011
DOI: 10.4103/0256-4947.84622
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and antibiotic susceptibility of gram-positive bacteria in Makkah hospitals

Abstract: BACKGROUND AND OBJECTIVE:Gram-positive bacteria are important nosocomial pathogens. The objective of this study was to estimate the frequencies and resistance rates of gram-positive pathogens isolated from hospitals in Makkah, Saudi Arabia.DESIGN AND SETTING:Prospective study at three Makkah hospitals from May 2008 to April 2009.PATIENTS AND METHODS:Clinical isolates were collected and demographic and laboratory data were recorded. Standard microbiological methods were used to identify the organisms and test f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 22 publications
0
28
0
2
Order By: Relevance
“…Transnational dissemination of multi-drug resistant organisms has been reported [28] . This is relevant in the context of pneumococcal disease since about 20% of the pneumococcal isolates at Hajj are penicillin resistant [53] . Circulation of drug resistant pneumococci has been of concern in other mass gatherings, such as the reporting of pathogenic multi-drug resistant strains of S. pneumoniae circulating in Spain at the time of Barcelona Olympic in 1992 (however, the Olympic Organising Committee did not recommend pneumococcal vaccine for visitors) [54,55] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transnational dissemination of multi-drug resistant organisms has been reported [28] . This is relevant in the context of pneumococcal disease since about 20% of the pneumococcal isolates at Hajj are penicillin resistant [53] . Circulation of drug resistant pneumococci has been of concern in other mass gatherings, such as the reporting of pathogenic multi-drug resistant strains of S. pneumoniae circulating in Spain at the time of Barcelona Olympic in 1992 (however, the Olympic Organising Committee did not recommend pneumococcal vaccine for visitors) [54,55] .…”
Section: Discussionmentioning
confidence: 99%
“…Circulation of drug resistant pneumococci has been of concern in other mass gatherings, such as the reporting of pathogenic multi-drug resistant strains of S. pneumoniae circulating in Spain at the time of Barcelona Olympic in 1992 (however, the Olympic Organising Committee did not recommend pneumococcal vaccine for visitors) [54,55] . Today, antibiotic resistance is widespread and, considering the high incidence of pneumonia, the high carriage rate of pneumococci and circulation of multi-drug-resistant pneumococci, vaccination is recommended for all high-risk pilgrims and the conjugate vaccine is preferred [20,37,53] . The effect of facemasks use on pharyngeal bacterial carriage at Hajj has not been established yet, although a large trial is underway to examine the effectiveness of facemasks against viral infections [32] .…”
Section: Discussionmentioning
confidence: 99%
“…[1518] This ranges between 30% and 40% in different regions of the neighboring country, Saudi Arabia. [19] MRSA frequency largely depends on several factors such as infection control activities and antimicrobial selection pressure. Regarding the first issue; for example, it has been demonstrated that rigorous infection control practices set by the government in the United Kingdom have resulted in the sharp fall in MRSA prevalence from 40-45% during 2001–2005 to 36% in 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, at three Makkah Hospitals in Saudi Arabia, Asghar reported that 82.4% of CONS were resistant to oxacillin. [19] Isolated CONS from Northern population of Jordan revealed the resistance rate of 98.2% and 97.3% to ampicillin and penicillin, respectively. [28] The resistance rate of Staphylococcus epidermidis to oxacillin at Imam Khomeini hospital in Tehran and Namazi Hospital in Shiraz was 57.1%[16] and 100%,[13] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from three hospitals in Mecca city reported that S. pneumoniae was the main isolate from age groups <10 and >40 with an incidence rate of 36.8% and 57.9, respectively. [ 35 ] In a report from a university hospital in Riyadh conducted between 2000 and 2004, 62% of pneumococcal isolates from all age groups and 83% of isolates from children aged <2 years were included in the PCV7. [ 36 ] In a recent large prospective population-based study of CAP in hospitalized adults in the USA, a pathogen was identified in 38% of patients and S. pneumoniae was the responsible pathogen in 5% of them.…”
Section: Epidemiologymentioning
confidence: 99%